Evaluation of Agricultural Land Used Planning in the 3 Villages of Phaing District, Xayabouly Province, Lao PDR - XAYKHAMMOUN, KhamAiy; SINGPA, Bounlam; BRIATIA, Xoxiong (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
Participatory Land Use Planning (PLUP) is one of the tasks in the socio-economic development plan in the country which in the past lacks monitoring results and local participation is still limited in the implementation of the national land allocation master plan. The purpose of the study is to evaluate the villagers' understanding of participatory land use planning and the results of the implementation of land use according to the map. This research study has identified 03 municipal villages of Phiang District, Xayabualy Province, using social principles in quantitative and qualitative studies. With the IBM SPSS 20 program, from the results of interviewing a sample group of 200 farmers, it has been shown that the benefits of people's understanding of the agricultural land use plan in 03 municipal villages of the district is still moderate to minimal. However, the understanding of the villagers in each aspect may not be a determinant of compliance, only a point that helps the process to speed up according to various factors such as differences in gender, age, education level, status, occupation, source of income and their monthly income of the people of the 03 villages. The variation value to the understanding is between 0.000 - 0.181 with a statistical difference of 95%. The source of income for the people in the village is from the sale of agricultural products (from the use of agricultural land) and they earn in a month between 500,000 kip and more than 2,000,000 kip. The results of this study show that the use of agricultural land in the village is used for agricultural production and the production has increased every year. It can be seen from the sale of agricultural products that there is an increase in the use of agricultural land which corresponds to the actual survey that the agricultural land has increased and the forest area has decreased. The results of the study show that the income of the people in agricultural production has increased. for the understanding of the villagers is still little. In the villages that do not have a process of promotion after planning, the factors of strengthening the leadership of the village land management committee together with external assistance are important factors for the management of land development to get good results.